Electron diffraction determines molecular absolute configuration in a pharmaceutical nanocrystal - Brázda, Petr; Palatinus, Lukáš; Babor, Martin (Science (New York, N.Y.), 2019)
Determination of the absolute configuration of organic molecules is essential in drug development and the subsequent approval process. We show that this determination is possible through electron diffraction using nanocrystalline material. Ab initio structure determination by electron diffraction has so far been limited to compounds that maintain their crystallinity after a dose of one electron per square angstrom or more. We present a complete structure analysis of a pharmaceutical cocrystal of sofosbuvir and l-proline, which is about one order of magnitude less stable. Data collection on multiple positions of a crystal and an advanced-intensity extraction procedure enabled us to solve the structure ab initio. We further show that dynamical diffraction effects are strong enough to permit unambiguous determination of the absolute structure of material composed of light scatterers.
Keywords: Antiviral Agents; Electrons; Drug Design; Nanoparticles; sofosbuvir; prolin; antivirové látky; elektrony; Sofosbuvir; difrakce rentgenového záření; X-Ray Diffraction; Proline; racionální návrh léčiv; nanočástice